Corporate tax changes and credit costs - Yota Deli; Manthos D. Delis; Iftekhar Hasan; Panagiotis N. Politsidis; Anthony Saunders (University College Dublin, UCD School of Economics, 2022)
We examine changes in the corporate tax rate across the U.S. and their implications on the pricing and quantity of loans. We find an asymmetric effect on the cost of credit: loan spreads decrease by approximately 5.9 basis points in response to a one percentage tax cut, but they are insensitive to corporate tax increases. Primarily, a debt restructuring effect (working via firm's leverage) and, secondarily, a credit supply effect (working via bank market power and bank capital) drive the easing effect of tax cuts on equilibrium loan pricing, while the effect on the equilibrium quantity of loans is insignificant.
Keywords: G21; F31; F33; F34; 330; Corporate taxation; Cost of credit; Syndicated loans; Loan demand; Loan supply